Medical Cluster in Skolkovo - Asadov, Alexander; Asadov, Andrey; Petrenko, Lyubov (project baikal, 2019)
The medical cluster, as an integral part of Skolkovo, tests modern approaches and formats in the field of medicine. It combines medical treatment, education and scientific activity. Our task was to put all this functions in a new quality architecture.
Keywords: Skolkovo; medical cluster; innovative look